Critical steps and troubleshooting in sample preparation for wood and phloem formation - Balzano, Angela (Les (Ljubljana), 2022)
We present a technical note that supplements published procedures on optimal sample preparation for performing wood and phloem formation analyses. Before beginning sampling, it is important to learn about the characteristics of the tree or shrub species to be investigated. Some tips are given how to use the Trephor tool in the best way, how to remove the outer hard bark (periderm), how microcores should be handled after removal from the tree, and how they should be oriented for embedding in paraffin, and cutting thin sections for microscopy. Possible defects that may result from improper handling are illustrated and discussed. We also present optimal images to accurately identify different cell development stages in phloem and xylem, which is particularly challenging in hardwoods and Mediterranean tree and shrub species.
Keywords: les; microscopic slides; microscopy; mikroskopiranje; mikroskopski preparati; nastajanje floema; nastajanje lesa; odpravljanje težav; odvzem vzorcev tkiva; phloem formation; priprava vzorcev; prostorninsko krčenje; tissue preparation; tissue sampling; troubleshooting; wood; xylogenesis